2019
DOI: 10.1038/s41598-019-41813-x
|View full text |Cite
|
Sign up to set email alerts
|

Liver proteomics unravel the metabolic pathways related to Feed Efficiency in beef cattle

Abstract: Improving nutrient utilization efficiency is essential for livestock, given the current scenario of increasing demand for animal protein and sustainable resource use. In this context, understanding the biology of feed efficiency (FE) in beef cattle allows the development of markers for identification and selection of best animals for animal production. Thus, 98 young Nellore bulls were evaluated for FE and at the end of the experiment liver samples from six High Feed Efficient (HFE) and six Low Feed Efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 73 publications
4
28
0
Order By: Relevance
“…The genetic modulation of the innate immune system supports our previous studies that demonstrate the relationship between feed efficiency and hepatic inflammation (5,9). Along with the genes related to complement cascade regulation, other genes with potential functional variations enriched for the innate immune system as BOLA, ECSIT, GLB1, ADA2, RIPK3, LILRA4, SIRPB1 and YEAR6.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The genetic modulation of the innate immune system supports our previous studies that demonstrate the relationship between feed efficiency and hepatic inflammation (5,9). Along with the genes related to complement cascade regulation, other genes with potential functional variations enriched for the innate immune system as BOLA, ECSIT, GLB1, ADA2, RIPK3, LILRA4, SIRPB1 and YEAR6.…”
Section: Discussionsupporting
confidence: 83%
“…Our group was the first to described a pathophysiological mechanism associated with FE in beef cattle: liver inflammation due to altered metabolism and/or bacterial translocation/infection (5), which was in part corroborated by others (6)(7)(8). We also unravel the metabolic pathways related to FE in Nellore cattle showing an increased bacterial load in low feed efficient animals (LFE) which is in part responsible for the hepatic lesions and inflammation in these animals (9).…”
Section: Introductionsupporting
confidence: 68%
“…As an example, for the cattle feed efficiency dataset, we found significant enrichment for genes falling in shapes 1 to 4 ( Supplementary Files 2 to 5 ), each shape capturing specific Biological Processes. The animals on the feed efficiency dataset have been already extensively characterized [ 9 , 10 , 25 , 26 , 27 , 28 ], with low feed efficiency being associated with inflammatory/immune response and altered lipid metabolism in liver. Interestingly, shape 4, the one presenting the higher number of genes and reflecting a higher number of positive correlations, is not enriched specifically for inflammatory/immune response, but for transcription-related terms, such as mRNA processing (FDR = 7.13 × 10 −19 ) and mRNA splicing (FDR = 4.54 × 10 −15 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that antigen processing and presentation play a key role in adaptive immunity in teleost fish (47,48). The antigen processing and presentation pathway was also enriched in beef cattle fed a mixture containing dry corn grain, corn silage, soybean, citrus pulp pellets, urea, calcareous, mineral salt, and potassium chloride (49). Our results showed that most of the proteins involved in antigen processing and presentation were significantly upregulated in Mix-based diets (Mix0.08 and Mix0.5), while those protein expressions were inhibited in Pg0.08.…”
Section: Effect Of Extract-based Diets On Regulating Immune System Fumentioning
confidence: 99%